2020
DOI: 10.1039/d0ta05552b
|View full text |Cite
|
Sign up to set email alerts
|

Measuring effective stiffness of Li-ion batteries via acoustic signal processing

Abstract: In this work we build upon acoustic-electrochemical correlations to investigate the relationships between sound wave structure and chemo-mechanical properties of a pouch cell battery. Cell thickness imaging and wave detection...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 29 publications
3
36
0
Order By: Relevance
“…The upper half of the map highlights the resonance, exemplified by the dark blue lines tracking the first few peaks; while the lower half tracks the back-wall echoes, demonstrated by the orange line. We emphasise that the latter delivers similar information to the through-transmission configurations adopted in prior studies 22,24,27 .…”
Section: Soc Monitoring With Layer Resolutionmentioning
confidence: 64%
“…The upper half of the map highlights the resonance, exemplified by the dark blue lines tracking the first few peaks; while the lower half tracks the back-wall echoes, demonstrated by the orange line. We emphasise that the latter delivers similar information to the through-transmission configurations adopted in prior studies 22,24,27 .…”
Section: Soc Monitoring With Layer Resolutionmentioning
confidence: 64%
“…However, W. Chang et al demonstrated the sensitivity of thickness detection can be improved to micron resolution when combined with in-situ transmission X-ray microscopy (TXM). [229] They combined the ultrasound acoustic detection with TXM to study the expansion and contraction of a pouch cell during cycling. Their expectation is that TXM has sufficient range and pixel resolution to measure both the total cell thickness and the average layer thicknesses, though it proved to be more difficult to image.…”
Section: In Operando Acoustic Detection Of LI Metal Platingmentioning
confidence: 99%
“…In this work, we combine operando acoustic, NMR, and magnetic resonance imaging (MRI) techniques to probe the coupled relationship between interface mechanics, interphase chemistry, and microstructural formation at the mesoscale and microscale. Operando acoustic transmission can detect changes in cell modulus, density, and expansion in conventional lithium-ion cells 21 , 22 . Acoustic transmission utilizes sound waves at ultrasound frequencies (typically between 1 and 10 MHz) which propagate through the cell layers, with sound speed and amplitude dependent on the mechanical properties of each layer 23 .…”
Section: Introductionmentioning
confidence: 99%